Pemanfaatan Biji Alpukat (Persea americana Mill.) dengan Penambahan Lilin Lebah (Beeswax) pada Pembuatan Edible Film - Agus Mulyadi; Faizah Hamzah; Farida Hanum Hamzah2 (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Avocado seed contain amylose which could be raw material of making edible film. However, edible film was resulted have durability to low water. Therefore, needed add material hidrofobic which would increase of durability to water of edible film one of is beeswax.This research was conducted experimentaly by used Complete Randomized Design (CRD) with five treatmens and three replications which followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatment in this research were B1 (beeswax 5%), B2 (beeswax 10%), B3 (beeswax 15%), B4 (beeswax 20%) and B5 (beeswax 25%). The results of variance analysis showed that addition of concentrations beeswax gave significantly affect on thickness, solubility, water of uptake and water of transfer edible film. The best formulations was obtained on the edible film with addition 5% beeswax which has thickness of 0.28 mm, solubility of 23.59%, water of uptake 313.35% and water of transfer 0.23 g.m-2.hour. Keywords: avocado seed, edible film, beeswax